(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
This study describes the characteristics of household market participation in avocado production. It investigates the approach required to overcome determinants of market participation among smallholders of avocado farmers in Shebedino woreda, SNNPRS, Ethiopia. The primary sources of the data are farm household surveys, focus group discussions, and key informant interviews. Two hundred twenty-eight households were selected using a purposive sampling technique. The data obtained were evaluated using Double-hurdle econometric models. The results of the binary probit model revealed that in the decision to sell, land size, family size, distance from the nearest market center, market information, access to media, and the total amount of avocado produced played a significant role. The truncated regression model indicated that the age of the household head, family size, market information and the total amount of avocado produced significantly affected the level of commercialization. The result showed that enhancing the efficient utilization of the existing limited farmland, family size, access to market information, and the total amount of avocado produced had a higher value and was seen as a critical opportunity to improve the lower-income farm households. As a result, better market information, family planning, and new technology like improved verity are required to increase demand for avocado produce and income generation. Concerned bodies need to establish a market center for the farmers around their home, increasing the probability of avocado market participation. The findings of this study may help in the development of appropriate policy intervention mechanisms to promote smallholder avocado commercialization in Sidama Zone. Int. J. Agril. Res. Innov. Tech. 13(1): 89-95, June 2023